Determinants of overfunding in reward-based crowdfunding - Felix Pinkow (Electronic Commerce Research, 2023)
While research on factors contributing to the success of a reward-based crowdfunding project is abundant, research dedicated to projects that were not only successful, but received significantly more funds than initially targeted—overfunded projects—is still scarce. Following a qualitative case-study approach, this study sought to shed light on this phenomenon through examining expert interviews with supporters and team members of an overfunded crowdfunding project considered a critical case. The results are divided into three phases that differentiate characteristics ascribed to the crowd, the project, and the communication. The main findings highlight the central role of the project founders' reputation and experience, that a positive sentiment among the crowd towards the project must be encouraged and maintained and that the core target group must be correctly identified and attracted. This core target group is crucial for attracting a broader audience, a mechanism that is supported if the project benefits from network effects. A narrative of the project as a vision or 'dream' of the project founders thereby contributes to creating a hype and 'social buzz'. Ultimately, this study contributes to reward-based crowdfunding literature through offering novel insights on project overfunding and illustrating possibilities for new and small ventures how to attract and maintain customers through reward-based crowdfunding.
Keywords: 380; Reward-based crowdfunding; Overfunding; Success factors; Framework; Entrepreneurial finance; Business venturing